The Omnibus Law “Job Creation Law” and the Expansion of Neoliberalism Affecting Workers in Indonesia - Alam, Bahrul (Universitas Brawijaya, 2026)
This study explains how Indonesia's Job Creation Law implements an asymmetric neoliberal expansion model across various industrial sectors and analyzes the structural corrections introduced by the new constitution. Using a qualitative socio-legal approach, the research combines textual and implementation analyses of Constitutional Court Decision No. 168/PUU-XXI/2023 with sectoral political economy data. Moving away from conventional critiques of labor deregulation, the findings suggest that neoliberal expansion operates as a form of segmented regulatory engineering, such as legalizing structural labor vulnerabilities in the manufacturing sector, excluding local labor through easing foreign worker (TKA) permits in capital-intensive industries, and exploiting deliberate legal gaps in the gig economy. Crucially, the study demonstrates that Constitutional Court Decision No. 168/PUU-XXI/2023 structurally arrested this destructive trajectory by invalidating 21 pivotal provisions. This paper contributes a novel analytical synthesis that integrates positive law with sectoral dynamics under the latest judicial framework.